1996
DOI: 10.1029/96gl00781
|View full text |Cite
|
Sign up to set email alerts
|

Grain‐size dependence of the rock magnetic properties for a natural maghemite

Abstract: The natural maghemite from the Robe River mining district (Australia) is shown to be thermally very stable. The maghemite/hematite inversion occurs at -650øC for sized fractions (250 gm to < 5 gm), enabling determination of T c for maghemite at 610øC. The maghemite is intimately intergrown with hematite and Js of the maghemite (corrected for the hematite content) is 64 Am2/kg ß Jrs, Hcr and H c range between 7.46 -10.18 Am2/kg, 16.90 -23.30 mT, and 6.38 -9.00 mT respectively, indicating PSD maghemite with grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 18 publications
4
39
0
1
Order By: Relevance
“…B cr was 22 š 1 mT, slightly lower than that of magnetite but comparable to literature values (e.g. natural maghemite ¾23 mT [33]). …”
Section: Magnetic Analysis Of Maghemite Samplessupporting
confidence: 51%
See 2 more Smart Citations
“…B cr was 22 š 1 mT, slightly lower than that of magnetite but comparable to literature values (e.g. natural maghemite ¾23 mT [33]). …”
Section: Magnetic Analysis Of Maghemite Samplessupporting
confidence: 51%
“…Comparable temperature ranges have been reported in the literature (e.g. 510º-660ºC [30], ¾650ºC [33]). The results indicate -like in the case of magnetite -that the seemingly similar conditions under which the two batches were synthesised do not rule out the possibility of differences in magnetic or structural characteristics of the samples.…”
Section: Magnetic Analysis Of Maghemite Samplesmentioning
confidence: 55%
See 1 more Smart Citation
“…• C (Özdemir & Banerjee 1984;Özdemir 1990;de Boer & Dekkers 1996;Dunlop &Özdemir 1997;de Boer et al 2001). Moreover, the high degree of reversibility of the curve at high temperatures suggests that this ash underwent the highest heating temperature.…”
Section: Susceptibility Variations At Temperatures Up To 700mentioning
confidence: 99%
“…Those parameters also indicate an upward decrease in grain size of the ferrimagnetic minerals between 215 and 170 mbsf at Site 1115 and 320 and 280 mbsf at Site 1109. De Boer and Dekkers (1996) showed that the grain-size dependence of rock magnetic parameters for PSD maghemite is less prominent than for magnetite. Variations in the rock magnetic parameters for our samples may therefore mainly reflect the grain-size changes in magnetite.…”
Section: Discussionmentioning
confidence: 99%